Optimization of Operational Services at Jakarta Container Terminal Using Genetic Algorithm - Ibrahim Tirta Sumadilaga; Sjarief Widjaja (Publikasi Indonesia, 2024)
Economic growth significantly impacts port activity, making container terminals essential for global goods distribution. Key equipment, such as Container Cranes (CC), Rubber-Tyred Gantry Cranes (RTGC), and Head Trucks (HT), is crucial for terminal performance. This study focuses on optimizing equipment productivity at the Jakarta Container Terminal to improve the flow of containers. Using descriptive analysis and optimization methods like Genetic Algorithm (GA) with computer software, the research aims to find effective solutions to enhance equipment productivity. Based on the analyzed results, it can be concluded that the comparison of actual data with the Genetic Algorithm method shows a difference of 0.42% Crane Quantity, 2.64% productivity capacity and 2.29% for F(x), The results obtained by using the GA optimization method are better than the actual data.